Economic Empowerment of Marine Fisherfolk through Self-Help Groups - Benadict , T G; Nair, Sreedhar P; Varughese, Ashish (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Self-Help Group is a community-based voluntary organisation that promote financial inclusion and empower marginalised communities. This study intended to examine the role of SHG in economic empowerment of traditional marine fisherfolk in Alleppey District. In order to conduct the studies, 380 responses were collected through a multi-stage random sampling technique using a structured interview schedule. Spearman Rank Correlation, Chi-square test and Kruskal Wallis Test were employed to analyse the proposed conceptual model, while descriptive statistical tools were used to interpret the demographic information of the respondents. The study outcome confirmed that SHG have a significant positive impact on the economic empowerment of marine fisherfolk in Alappuzha. However, inefficiencies in leadership, inadequate in market linkages and insufficient training programs still remain as crucial challenges. Therefore, measures must be taken to improve training and leadership among SHG members to be more satisfied, eventually become economically empowered.